New Tricks for an Old (Hedge)Hog: Sonic Hedgehog Regulation of Astrocyte Function - A. Denise R. Garcia (Cells, 2021)
The Sonic hedgehog (Shh) molecular signaling pathway is well established as a key regulator of neurodevelopment. It regulates diverse cellular behaviors, and its functions vary with respect to cell type, region, and developmental stage, reflecting the incredible pleiotropy of this molecular signaling pathway. Although it is best understood for its roles in development, Shh signaling persists into adulthood and is emerging as an important regulator of astrocyte function. Astrocytes play central roles in a broad array of nervous system functions, including synapse formation and function as well as coordination and orchestration of CNS inflammatory responses in pathological states. Neurons are the source of Shh in the adult, suggesting that Shh signaling mediates neuron–astrocyte communication, a novel role for this multifaceted pathway. Multiple roles for Shh signaling in astrocytes are increasingly being identified, including regulation of astrocyte identity, modulation of synaptic organization, and limitation of inflammation. This review discusses these novel roles for Shh signaling in regulating diverse astrocyte functions in the healthy brain and in pathology.